2022
DOI: 10.7600/jpfsm.11.35
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure is lower in Japanese female athletes with menstrual disorders than in eumenorrheic athletes

Abstract: Menstrual disorders are health problems in female athletes. It has also been reported that amenorrhea can lead to metabolic suppression. However, studies regarding resting energy expenditure (REE) in Japanese female athletes with menstrual disorders are lacking. The purpose of this study was to investigate whether REE was suppressed in female Japanese athletes with menstrual disorders. In total, 22 highly trained intercollegiate athletes participated in this study; and body composition, REE, thyroid and reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In response to periods of low EA, the hypothalamic-pituitary-thyroid axis adapts to reduce energy expenditure ( 26 ). Athletes with menstrual disorders have demonstrated consistently decreased triiodothyronine (T 3 ) levels ( 9 , 27 ), therefore, a low T 3 level is one objective blood marker that could be used to identify female athletes with low EA. In exercising men, it has been reported that leptin and insulin are reduced, independent of whether low EA had originally occurred with or without exercise; however, low EA did not significantly impact ghrelin, T 3 , testosterone, and insulin-like growth factor-1 (IGF-1) levels ( 28 ).…”
Section: Alternative Methods For Detecting Low Ea Without Measurement...mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to periods of low EA, the hypothalamic-pituitary-thyroid axis adapts to reduce energy expenditure ( 26 ). Athletes with menstrual disorders have demonstrated consistently decreased triiodothyronine (T 3 ) levels ( 9 , 27 ), therefore, a low T 3 level is one objective blood marker that could be used to identify female athletes with low EA. In exercising men, it has been reported that leptin and insulin are reduced, independent of whether low EA had originally occurred with or without exercise; however, low EA did not significantly impact ghrelin, T 3 , testosterone, and insulin-like growth factor-1 (IGF-1) levels ( 28 ).…”
Section: Alternative Methods For Detecting Low Ea Without Measurement...mentioning
confidence: 99%
“…Since the introduction of EA in 2007 ( 5 ), numerous researchers have assessed EA in athletes with equivocal results, due in part to no clear methodological guidelines for calculating EA, including techniques used to measure each component of the EA equation ( 6 , 7 ). For example, female athletes with similar EI had different menstrual conditions (eumenorrheic or amenorrheic) ( 8 , 9 ), while in males, EI is similar between cross-country athletes and sedentary controls ( 10 ). Conversely, the mean EEE in female and male athletes at risk for low EA was significantly higher than moderate or no-risk athletes ( 11 , 12 ), suggesting that in athletes, high EEE affects EA values.…”
Section: Introductionmentioning
confidence: 99%